Public Space as a Necessity for a Flexible and Effective Strategic Public Management: The Opportunity of Independent Agencies - Platis, Charalampos; Kopsidas, Odysseas; Kokiousi, Maria Vasiliki; Raptis , Athanasios E.P. (SPOUDAI Journal of Economics and Business, 2020)
This paper seeks to present the necessity of the public “space” availability as a relaxation of the legislation margins in order of a flexible and efficient Strategic Public Management. This papers is about to be proposed with inclusion of the basic ideas of public strategic management. The proposed strategic plan is supposed to be adopted by an Independent Authority in Greece, the Ombudsman, which is a part of Hellenic Public Administration. The enhanced Bryson model of strategic public administration was selected, as the basis for this application. The whole strategic plan development methodology constitutes from the hyper thesis of several models, while each Bryson step, may assumed as a discrete method, as well as an implementation of qualitative and quantitative analysis such as text analysis and regression analysis. The Balanced Scorecard business model was performed, with regards to breaking down strategic goals to operational and individual. The final outcome of the strategic planning methodology in the Greek Ombudsman is that according to the strategic mapping model, the focus should be placed on the citizen as a user of the services and the rest of the operational goals should be set in such a way as to allow and guide the Ombudsman’s services around the citizen’s needs. As a basic finding of the whole application is the need for extended flexibility of such organization in terms of self-determining the vision and the operational goals. JEL Classification: H11, H83, C88